Maximum stress analysis for dam structure due to different magnitude scales of ground movements - Zawawi M.H.; Itam Z.; Saleha A.; Ramli M.Z.; Hassan N.H.; Zahari N.M.; Salwa A.; Muda Z.C. (American Institute of Physics Inc., 2023)
This study is aimed to evaluate maximum stress analysis for dam stability due to ground movement on Chenderoh dam in Perak. The dam was constructed in the year 1930s, therefore it is important to examine the dam workability and integrity for the peoples to take caution and prepared for safety. Initially, the analysis using ABAQUS is to verify the available data obtained from Structural Earthquakes Research Malaysia. The data available is the maximum stress of 108.67 kN/m2 for seismic load of 0.16g. Validation for this data after running the ABAQUS program shows that it is in good agreement with the available data, that is the result at 0.16g, the maximum stress is 112 kN/m2. Using this data for example concrete grade 20 N/m2, the maximum stress at 0.16G, 0.20g and 0.25g are analyzed. The significant of this study is that at 0.25g seismic acceleration, the dam is still stable as the stress at 0.25g does not exceed the available maximum stress of the material. 2018 Author(s).